Photocatalytic reduction of Cr(VI) by PVA-alginate encapsulated γFe 2O 3 magnetic beads using different types of illumination lamp and light - Idris, Ani (The Korean Society of Industrial and Engineering Chemistry, 2012)
In this study the toxic Cr(VI) which is a common pollutant to the environment is removed from the aqueous solution using the one step photocatalytic reduction to Cr(III) using PVA-alginate encapsulated γFe 2O 3 magnetic beads. The photocatalytic reduction of Cr(VI) by PVA-alginate encapsulated γFe 2O 3 magnetic beads was examined under sunlight and other 4 types of lamp: xenon lamp, black light bulb (BLB) lamp, light emitting diode (LED) lamp and fluorescent lamp. The experiments were performed at pH 1, initial Cr(VI)=50mg/L and the photocatalyst dosage of maghemite nanoparticles was kept at 8% (v/v). Removal of Cr(VI) was best under sunlight; 100% removal in 30min, followed by xenon lamp; 100% removal in 100min, BLB lamp; 70% removal in 100min. LED and fluorescent lamp have about the same removal rate; 50% removal in 100min. The Cr(VI) reduction using PVA-alginate magnetic beads fitted the Langmuir-Hinshelwood (L-H) kinetics model with a correlation coefficient (R 2) of 0.972. The PVA-alginate magnetic beads were capable of treating industrial chromium waste containing 300mg/L Cr(VI) within 2h under sunlight.